2018
DOI: 10.1007/s10238-018-0489-2
|View full text |Cite
|
Sign up to set email alerts
|

Is the 1298A>C polymorphism in the MTHFR gene a risk factor for arterial ischaemic stroke in children? The results of meta-analysis

Abstract: An elevated level of homocysteine is a risk factor for vascular diseases, brain atrophy and several other disorders. The 1298A>C polymorphism (rs1801131) leads to mildly decreased MTHFR activity. Previously, it was observed that the MTHFR 1298A>C polymorphism in combined analysis with the MTHFR 677C>T polymorphism increases homocysteine levels. However, conflicting results on its relation to ischaemic stroke in children can be found. We conducted a meta-analysis to analyse possible connections between the MTHF… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 46 publications
(64 reference statements)
0
6
0
Order By: Relevance
“…Incomplete article search may lead to unstable results. Later a meta-analysis study performed in 2018 reported the association among MTHFR A1298C polymorphism and IS risk [ 15 ]. In recent years, many studies [ 16 – 20 ] have reported the association among MTHFR A1298C polymorphism and stroke risk.…”
Section: Introductionmentioning
confidence: 99%
“…Incomplete article search may lead to unstable results. Later a meta-analysis study performed in 2018 reported the association among MTHFR A1298C polymorphism and IS risk [ 15 ]. In recent years, many studies [ 16 – 20 ] have reported the association among MTHFR A1298C polymorphism and stroke risk.…”
Section: Introductionmentioning
confidence: 99%
“…A meta-analysis by Zhang et al included 15 studies showing the effect of A1298C polymorphism on adult IS, mainly in Asian populations [36]. Sarecka-Hujar et al performed a meta-analysis to evaluate the relationship between this variant and IS in pediatric patients in eight case-control studies, and found no association between this polymorphism and IS in children—for neither the recessive nor the additive models nor the allelic models [37]. Wei et al (490 case-control studies) reported the association between MTHFR A1298C and C677T polymorphisms and IS [38].…”
Section: Discussionmentioning
confidence: 99%
“…The methodological quality of the studies included was examined with the use of the Newcastle-Ottawa scale for case–control studies 27,28 with the scores ranged from 0 points to 11 points. We accepted study as a high quality with a score of 5 or higher.…”
Section: Methodsmentioning
confidence: 99%